Nerve ECM and PLA-PCL based electrospun bilayer nerve conduit for nerve regeneration - Mao, Xiaoyan; Li, Ting; Cheng, Junqiu; Tao, Meihan; Li, Zhiyuan; Ma, Yizhan; Javed, Rabia; Bao, Jie; Liang, Fang; Guo, Weihong; Tian, Xiaohong; Fan, Jun; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
The porcine nerve-derived extracellular matrix (ECM) fabricated as films has good performance in peripheral nerve regeneration. However, when constructed as conduits to bridge nerve defects, ECM lacks sufficient mechanical strength. In this study, a novel electrospun bilayer-structured nerve conduit (BNC) with outer poly (L-lactic acid-co-ε-caprolactone) (PLA-PCL) and inner ECM was fabricated for nerve regeneration. The composition, structure, and mechanical strength of BNC were characterized. Then BNC biosafety was evaluated by cytotoxicity, subcutaneous implantation, and cell affinity tests. Furthermore, BNC was used to bridge 10-mm rat sciatic nerve defect, and nerve functional recovery was assessed by walking track, electrophysiology, and histomorphology analyses. Our results demonstrate that BNC has a network of nanofibers and retains some bioactive molecules, including collagen I, collagen IV, laminin, fibronectin, glycosaminoglycans, nerve growth factor, and brain-derived neurotrophic factor. Biomechanical analysis proves that PLA-PCL improves the BNC mechanical properties, compared with single ECM conduit (ENC). The functional evaluation of in vivo results indicated that BNC is more effective in nerve regeneration than PLA-PCL conduit or ENC. In conclusion, BNC not only retains the good biocompatibility and bioactivity of ECM, but also obtains the appropriate mechanical strength from PLA-PCL, which has great potential for clinical repair of nerve defects.